The dog who saved the bees - Gibeault, Stephanie (Sleeping Bear Press, 2025)
"The true story of beehive inspector, Cybil Preston, and her work with Mack, an unruly rescue dog, to save commercial bee beehives from foulbrood, a deadly disease with no cure that has decimated American bee populations"-- Provided by publisher.